Determination of plasma transcobalamin-II and zinc levels in newly–diagnosed and long–standing grand mal epileptic patients - Amene Aman-Mohammady; Payam Saadat; Durdi Qujeq; Karimollah Hajian-Tilaki; Kiarash Saleki (Caspian Journal of Internal Medicine, 2023)
Background: The changes of plasma transcobalamin-II (TCII) and Zinc (Zn) Levels in epileptic patients are not clearly understood. The aim of the current study was to evaluate the plasma contents of TCII and Zn levels in newly–diagnosed epileptic seizure patients, long-standing grand mal epileptic patients following treatment with sodium valproate and healthy control group. Methods: Thirty patients aged 36.76±12.91 years with newly–diagnosed and thirty long-standing grand mal epileptic patients aged 35.56 ±12.77 years were diagnosed based on the clinical symptoms. The control subjects were picked out from healthy individuals and matched to the patients, aged 36.30 ±12.80 years. Plasma Zn and TCN-2 was evaluated via spectrophotometry at 546 nm and 450 nm, respectively, using chimerical kits. Results: Plasma level of TCII in the newly–diagnosed epileptic seizures patients and long-standing grand mal epileptic patients were significantly increased, compared to the healthy controls [14.89 ±3.24 and 21.84± 2.73 vs. 9.55±1.24, (n=30)], respectively. Plasma level of Zn was decreased in the newly–diagnosed epileptic seizure patients, while it was increased in long-standing grand mal epileptic patients compared to the control group [69.28± 6.41 and 80.56 ±6.12 and vs.75.80±1.59, (n=30)], respectively. Conclusion: This study suggests that sodium valproate may disrupt the homeostatic balance of TCII and Zn, and cause abnormality of their serum level in newly–diagnosed epileptic seizure patients and long-standing grand mal epileptic patients. Further research is recommended to identify the underpinning for these changes.